0703 Development of the Obstructive Sleep Apnea Questionnaire for Use in Clinical Practice. (25th May 2022) - Kirsch, Douglas; Abbasi-Feinberg, Fariha; Davies, Charles; Gamaldo, Charlene; Rosen, Carol; Thomas, Sherene; Koochaki, Patricia; Lipman, Kelly; Hall, Nicolas
Abstract: Introduction: An American Academy of Sleep Medicine (AASM) task force identified a need for a valid, reliable, patient-reported outcome measure (PROM) to monitor obstructive sleep apnea (OSA) in adults in clinical practice. Ideally, the PROM should be easy and quick to complete (<5 minutes), available electronically, and accepted by clinicians treating OSA. Development of the Obstructive Sleep Apnea Questionnaire (OSA-Q) was undertaken to meet this need and was guided by the 2009 Food and Drug Administration (FDA) Guidance for Industry on developing PROMs. Methods: Development of the OSA-Q included interviews with patients with OSA (n=14) to identify important concepts to them, conceptual model and draft questionnaire formulation, and cognitive interviews (n=14) to assess content validity and guide revisions to wording, item comprehension and redundancies, recall period, and response options. Usability of the electronic version of the OSA-Q was then assessed in patients with OSA. Finally, acceptability and utility of the OSA-Q in clinical practice was evaluated by surveying clinicians in ten geographically-dispersed US sleep clinics. Results: Patient interviews were used to construct a conceptual model for the draft OSA-Q which served as a basis for generating 44 items about daytime/night-time symptoms and OSA impacts. Cognitive interviews identified poorly worded, ambiguous, and redundant items to inform revisions, resulting in a revised draft OSA-Q (3 domains, 28 items). Subsequently, clinicians (n=13) administered the draft OSA-Q to five patients each, obtained patients' feedback on the OSA-Q, and completed a survey regarding its comprehensiveness, format/content, utility, and acceptability in clinical practice. These clinicians endorsed the OSA-Q for ease of use, language simplicity, convenience of electronic platform, and speed of completion (3-5 min). They also indicated that the OSA-Q would be useful in clinical practice and enhance patient communications (69% and 77%, respectively). The OSA-Q was revised and finalized for psychometric testing, based on clinician comments. Conclusion: A new AASM-supported PROM to monitor OSA in clinical practice has been developed, including the patients' perspective according to FDA guidance. This OSA-Q shows content validity and is positively perceived by clinicians. Psychometric testing of the OSA-Q is underway to establish its measurement properties and demonstrate its validity, reliability, and sensitivity to change in patients with OSA. Support (If Any): This work was funded by the American Academy of Sleep Medicine.